1978
DOI: 10.1203/00006450-197804001-01179
|View full text |Cite
|
Sign up to set email alerts
|

1173 Comparison of Chest Physiotherapy Techniques in Infants With HMD

Abstract: (Spon. by L.J. Butterfield). The pressure in an infant's airway when CPAP is delivered by nasal prongs has not been previously repor ted. Using air-filled catheters and differential pres sure transducers we have measured simultaneous pressures in nasal prongs (Ppr) and pharynx(Ppx) in 1 8 newborns. After a steady state was achieved, end expi ratory pressure in five consecutive breaths was measured: these were usually identical but otherwise were averaged. The pressure difference (Ppr-PpXsAP) was lo in infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1981
1981
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…37 A study comparing four different combinations of CPT techniques found slightly higher systolic blood pressure in infants treated in the head down position. 38 In that study, neither heart rate nor blood pressure increased beyond normal ranges.…”
Section: Review Of Literature: Effects Of Cpt In Neonatesmentioning
confidence: 70%
See 2 more Smart Citations
“…37 A study comparing four different combinations of CPT techniques found slightly higher systolic blood pressure in infants treated in the head down position. 38 In that study, neither heart rate nor blood pressure increased beyond normal ranges.…”
Section: Review Of Literature: Effects Of Cpt In Neonatesmentioning
confidence: 70%
“…Crane and co-workers compared percussion with vibration in two different drainage positions. 38 No significant difference in TCPO 2 was found 30 minutes before and 5, 15, and 60 minutes after CPT. When percussion was used, there was a trend toward higher TCPO 2 values up to one hour after treatment.…”
Section: Percussion and Vibrationmentioning
confidence: 81%
See 1 more Smart Citation
“…O estudo de Gava e Picanço 42 aponta que a tapotagem por si só não é capaz de promover eliminação das secreções, mas aumenta a velocidade de eliminação do muco 37,43,44 . Retificando o estudo anterior, Crane et al 44 observaram em sua pesquisa realizada com 24 RNPT com síndrome do desconforto respiratório e em oxigenoterapia, sendo que 16 neonatos estavam sob uso da ventilação mecânica. Os autores compararam a tapotagem e a vibração em duas posições de drenagem postural.…”
Section: Resultsunclassified
“…Head-down positioning may, however, increase systemic blood pressure with the potential for intraventricular hemorrhage in neonates, increase gastroesophageal reflux and intracranial pressure, place the diaphragm at mechanical disadvantage, and may increase venous return, thereby increasing the work of the heart. 23,[40][41][42][43] Conversely, the upright position has been shown to improve end-expiratory lung volumes (keeping the functional residual capacity above closing capacity and therefore preventing airway closure) and oxygenation, and may protect against ventilator-associated pneumonia. [44][45][46][47] Considering the lack of supporting evidence and the potential for adverse events, the inverted position should not be used in pediatric practice.…”
Section: Positioningmentioning
confidence: 99%